Physiotherapy Management To Prevent Covid-19 By Improved Physical Activity In Elderly - Rakasiwi, Andung Maheswara; Nahdliyyah, Ade Irma (Journal Research of Social Science, Economics, and Management, 2023)
Coronavirus 2019 (Covid 19) is an acute respiratory syn-drome caused by the corona-2 virus (SARS-CoV-2). Meanwhile, elderly is a condition characterized by a decline in the tissue's self-repairing func-tion. This decline causes various diseases and health problems, hence, efforts are needed to improve their physical condition and health after retirement. Therefore, this study aims to reduce the impact of Covid-19 on the elderly as well as to provide an overview of the physical problems associated with the virus and its prevention measures. This is an experimental study with a pre-experimental research design in the form of a one-group pre-post-test design. The results showed a probability with a p-value of <0.05, which indicates that physiotherapy management in the elderly during Covid-19 increased their physical activity, thereby eliminating the risk of exposure to the virus. The statistical analysis results showed that there was a sig-nificant difference between the pre-test and post-test on physiotherapy management. Furthermore, physical activity had a p-value of 0.015, which indicates that the level of physical activities carried out did not change, but it served as a motivation. The fear of contracting the virus had a p-value of 0.007, which shows that information on physical activity provided by physiotherapists had no effect on their fea.